Simulating Societal Change Counterfactual Modelling for Social and Policy Inquiry - Davis, Peter; Lay-Yee, Roy (Computational Social Sciences,, 2019)
This book presents a method for creating a working model of society, using data systems and simulation techniques, that can be used for testing propositions of scientific and policy nature. The model is based on the example of New Zealand, but will be applicable to other countries. It is expected that collaborators in other countries can emulate this example with their data systems for teaching and policy purposes, producing a cross-national "collaboratory". This enterprise will evolve with, and to a degree independently of, the book itself, with a supporting website as well as teaching and scientific initiatives. Readers of this text will, for the first time, have a simulation-based working model of society that can be interrogated for policy and substantive purposes. This book will appeal to researchers and professionals from various disciplines working within the social sciences, particularly on matters of demography and public policy.